2021
DOI: 10.3390/ijms222111860
|View full text |Cite
|
Sign up to set email alerts
|

FLLL32 Triggers Caspase-Mediated Apoptotic Cell Death in Human Oral Cancer Cells by Regulating the p38 Pathway

Abstract: Oral cancer is the most common oral malignant tumor in Taiwan. Although there exist several methods for treatment, oral cancer still has a poor prognosis and high recurrence. FLLL32, a synthetic analog of curcumin with antitumor activity, is currently known to induce melanoma apoptosis and inhibit tumor growth in various cancers. However, few studies have examined the mechanisms of FLLL32 in oral cancer. In this study, we explore whether FLLL32 induces apoptosis in oral cancer. We determined that FLLL32 can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The inhibitors were U0126, 46 JNK‐IN‐8 47 and SB203580 48 for blocking the phosphorylation of ERK1/2, JNK1/2 and p38 respectively. According to previous studies, 49,50 after 2‐hour pretreatments of U0126 (10 µM), JNK‐IN‐8 (10 µM) and SB203580 (10 µM), cells were administered with HO‐3867 (20 µM) for another 24 h. We found the treatment of JNK‐IN‐8 was able to attenuate the formation of the active form of caspase 3, caspase 8, caspase 9 and PARP in SCC‐9 cells (Figure 7A). Moreover, as shown in Figure 7B, inhibition of JNK1/2 pathway using JNK‐IN‐8 (10 µM) effectively reduced the apoptotic pathway as the active form of caspase 3, caspase 8, caspase 9 and PARP were reduced in HSC‐3 cells (Figure 7B).…”
Section: Resultsmentioning
confidence: 52%
“…The inhibitors were U0126, 46 JNK‐IN‐8 47 and SB203580 48 for blocking the phosphorylation of ERK1/2, JNK1/2 and p38 respectively. According to previous studies, 49,50 after 2‐hour pretreatments of U0126 (10 µM), JNK‐IN‐8 (10 µM) and SB203580 (10 µM), cells were administered with HO‐3867 (20 µM) for another 24 h. We found the treatment of JNK‐IN‐8 was able to attenuate the formation of the active form of caspase 3, caspase 8, caspase 9 and PARP in SCC‐9 cells (Figure 7A). Moreover, as shown in Figure 7B, inhibition of JNK1/2 pathway using JNK‐IN‐8 (10 µM) effectively reduced the apoptotic pathway as the active form of caspase 3, caspase 8, caspase 9 and PARP were reduced in HSC‐3 cells (Figure 7B).…”
Section: Resultsmentioning
confidence: 52%
“…Upstream of Akt, downregulation of the MAPK/ERK protein serine kinase MEK2 (MA2K2) was also reported (Chiu et al, 2021), thus, effectively, inhibiting proliferation and inducing apoptosis by curcuminoids in cancer cells can involve the p38 MAPK pathway (He et al, 2021;Su et al, 2021) (Figure 3). Blocking ERK1/2 expression in glioma cells by curcumin was also observed in another study, confirming that the MAPK signaling pathway is a potential target (Wang P. et al, 2021).…”
Section: Molecular and Cellular Cancer Emt: Targets Of Curcuminoidsmentioning
confidence: 80%
“…Some studies reported that p38MAPK signal pathway proteins may be related to the regulation of apoptosis genes [ 33 ], or play a role in antitumor drugs activity [ 34 ]. Blockage of the p38MAPK pathway inhibits tumor cells apoptosis [ 35 ]. However, no study has examined the role p38MAPK plays in TanIIA–induced apoptosis in human colorectal tumor cells.…”
Section: Discussionmentioning
confidence: 99%